GeV electron beams from a centimeter-scale channel guided laser wakefield accelerator - Nakamura, K; Nagler, B; Toth, C; Geddes, C; Schroeder, C; Esarey, E; Leemans, W; Gonsalves, A; Hooker, S (2007)
Laser wakefield accelerators can produce electric fields of order 10-100 GV/m, suitable for acceleration of electrons to relativistic energies. The wakefields are excited by a relativistically intense laser pulse propagating through a plasma and have a phase velocity determined by the group velocity of the light pulse. Two important effects that can limit the acceleration distance and hence the net energy gain obtained by an electron are diffraction of the drive laser pulse and particle-wake dephasing. Diffraction of a focused ultrashort laser pulse can be overcome by using preformed plasma channels. The dephasing limit can be increased by operating at a lower plasma density, since this results in an increase in the laser group velocity. Here we present detailed results on the generation of GeV-class electron beams using an intense femtosecond laser beam and a 3.3 cm long preformed discharge-based plasma channel [W. P. Leemans et al., Nature Physics 2, 696 (2006)]. The use of a discharge-based waveguide permitted operation at an order of magnitude lower density and 15 times longer distance than in previous experiments that relied on laser preformed plasma channels. Laser pulses with peak power ranging from 10-40 TW were guided over more than 20 Rayleigh ranges and high quality electron beams with energy up to 1 GeV were obtained by channeling a 40 TW peak power laser pulse. The dependence of the electron beam characteristics on capillary properties, plasma density, and laser parameters are discussed. (C) 2007 American Institute of Physics.